Mangroves of the Tropical East Pacific - Montes Chaura, Camilo (2024)
Mangroves of the Tropical East Pacific (TEP) province is a regional ecosystem subgroup (Level 4 unit of the IUCN Global Ecosystem Typology), present in the coastal ecoregions of the Mexican Tropical Pacific, Chiapas-Nicaragua, Nicoya, Panama Bight, and Guayaquil. In 2020, mangroves cover 7782 km2 in the province, representing 5.3% of the global coverage. In the province, there are eight true mangrove species; however, regional experts recognize other related plants classified as associated plants. The IUCN Red List includes 224 species (217 Animalia and seven Plantae species), supported by records in the Global Biodiversity Information Facility GBIF. It is estimated that the mangroves of the TEP showed a net change of -1.9% from 1996 to 2020; under this trend, a decrease of 3.3% is projected in 50 years, which is below 30%, classifying criterion A2 as least concern. However, based on indicative figures, a decrease of around 40% was estimated in the last 50 years (1970-2020); which as this exceeds 30%, the mangroves are vulnerable under Criterion A1. Although threats such as deforestation, human activities, pollution, infrastructure development, modification of natural systems, and invasion of exotic species are reported, none promote total disappearance; therefore, criteria B3 is classified as least concern. In a SLR scenario (IPCC RCP8.5), ≈ 9.8% of the TEP mangroves would be submerged by 2060, which is below the 30% risk threshold for criterion C2. Furthermore, 1.5% of the province's mangrove is suffering degradation, with the potential to increase to 4.5% over 50-year period; this ranks the mangroves as least concern under criterion D2b. Overall, the Tropical East Pacific mangrove ecosystem was assessed as Vulnerable (VU) with the available information. It is considered that there is insufficient data to assess the other criteria, therefore, it is recommended to update the data to increase the precision of the evaluation and enable the quantitative analysis of risks.